Hydroxyapatite cages with aligned pores for bone grafting – Seeding of human osteoblast-like cells in vitro and their response in dynamic culture mode. Issue 21 (1st November 2021) - Athira, R.K.; Gayathry, G.; Anil Kumar, P.R.; Harikrishna Varma, P.R.; Kasoju, Naresh; Komath, Manoj
Abstract: Hydroxyapatite (HA) is a highly regarded synthetic bone graft material. Porous HA ceramics blocks are used to substitute harvested natural bone grafts. Being similar to bone mineral, HA material integrates with the host bone through surface osteointegration and slowly resorb along with the natural bone remodeling process. The blocks in use currently have random and tortuous pore structures. The present work explores the usefulness of cage-like HA ceramic design with end-to-end open pores, with the help of in vitro cell culture methods. Such a structure, on implantation, will take up the blood factors and cells and host the bone remodeling process inside the bulk of the cage, leading to early healing. In the study, HA samples with aligned through-pores were prepared and explored in vitro, with a focus on how the pores host the cells inside and to what level the cells maintain their activity. Human osteoblast-like cells (HOS) were used, at different seeding and culturing approaches. Cell seeding was done through (i) conventional large volume cell suspension, (ii) a confined mini chamber with a limited volume of cell suspension, and (iii) placing a concentrated drop of cell suspension directly on top of the scaffold. The third approach gave the best cell adhesion and proliferation, and hence used for further explorations. A dynamic culture system was designed in-house by bifurcating the cell culture wells using vertical inserts, holding the samples horizontally with their ends open to both sides, and making the media flow across using a rocker platform. The HOS cell adhesion, viability and proliferation were tested in the HA cages, in static and dynamic culture conditions, with conventional porous ceramics as the control. The cell infiltration was deeper and the cell viability over a period of 7 days was significantly higher in dynamic culture conditions in the test samples.